IMPROVING THE ACCOUNTING AND DISTRIBUTION OF OVERHEAD COSTS BASED ON THE USE OF FUNCTIONAL COST ACCOUNTING AND ABC SYSTEM - G. A. Adamova; L. Sh. Zhafyarova (Вестник университета, 2021)
The article carries out a critical analysis of the traditional approach to costing. The paper reveals the problem of distortion of the cost of manufactured products from the point of view of making management decisions. The authors justify the expediency of using the ABC system for accounting and distribution of overhead costs. The study gives the interpretation of the concepts used in the functional distribution of costs. The article highlights and discloses a step-by-step algorithm for the distribution of indirect costs when using the ABC system. The paper gives the advantages of using this approach in order to generate management information about the products and activities of the company. Along with that, the authors analysed the difficulties associated with the practical implementation of the functional approach in the accounting and distribution of overhead costs, in particular with the detailed information in the context of operations and cost pools.